Microstructured chalcogenide optical fibers from As2S3 glass: towards new IR broadband sources - El-Amraoui, M.; Gadret, G.; Jules, J. C.; Fatome, J.; Fortier, C.; Desevedavy, F.; Skripatchev, I. [UNESP]; Messaddeq, Younes [UNESP]; Troles, J.; Brilland, L.; Gao, W.; Suzuki, T.; et al. (Optical Soc Amer, 2010)
The aim of this paper is to present an overview of the recent achievements of our group in the fabrication and optical characterizations of As2S3 microstructured optical fibers (MOFs). Firstly, we study the synthesis of high purity arsenic sulfide glasses. Then we describe the use of a versatile process using mechanical drilling for the preparation of preforms and then the drawing of MOFs including suspended core fibers. Low losses MOFs are obtained by this way, with background level of losses reaching less than 0.5 dB/m. Optical characterizations of these fibers are then reported, especially dispersion measurements. The feasibility of all-optical regeneration based on a Mamyshev regenerator is investigated, and the generation of a broadband spectrum between 1 mu m and 2.6 mu m by femto second pumping around 1.5 mu m is presented. (C) 2010 Optical Society of America